Kinetics of Complex Reaction of Eugenol Hydrogenation to 2-Methoxy-4-Propylphenol in Pd/Y Catalyst - Asep Kadarohman (Jurnal ILMU DASAR, 2010)
Eugenol and isoeugenol hydrogenations using Pt, Pd, Ni as a single or combined metal, that was supported on X and Y zeolite have been carried out. The experiment result showed that in hydrogenation reaction using metal that was supported on zeolite, eugenol is more easily hydrogenated than isoeugenol. Pd metal that was supported on Y zeolite as a catalyst in eugenol hydrogenation is more effective than Ni, Pt or combined metal (Pt,Pd,Ni/X). The highest conversion selectivity of eugenol hydrogenation is in 6% catalyst of Pd (10%)/Y that produced 98.24% of 2-methoxy-4- propylphenol. Kinetic of reaction is very important data that is needed in processing for industry scale, because kinetic can show how fast the starting material is converted into products. In this research, kinetic of the reaction was done by eugenol hydrogenation at 245oC with variation of time using Pd/Y catalyst. The result shows that eugenol hydrogenation is a complex reaction, because the reaction yields not only 2-methoxy-4-propylphenol as a main product, but also cis-isoeugenol and trans-isoeugenol as the side products. The reaction pathway of eugenol hydrogenation in Pd/Y catalyst is a combination of parallel and consecutive pathway and pseudo first order reaction with k = 0.5509.